2011
DOI: 10.2174/157340311797484231
|View full text |Cite
|
Sign up to set email alerts
|

Heart Transplantation for Congenital Heart Disease in the First Year of Life

Abstract: Successful infant heart transplantation has now been performed for over 25 years. Assessment of long term outcomes is now possible. We report clinical outcomes for322 patients who received their heart transplant during infancy. Actuarial graft survival for newborn recipients is 59% at 25 years. Survival has improved in the most recent era. Cardiac allograft vasculopathy is the most important late cause of death with an actuarial incidence at 25 years of 35%. Post-transplant lymphoma is estimated to occur in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 41 publications
2
52
2
2
Order By: Relevance
“…Chinnock et al included neonates in his report on the Loma Linda infant experience in 2011 (6). Heart transplants were accomplished in 103 neonates from 1985 to 2010.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chinnock et al included neonates in his report on the Loma Linda infant experience in 2011 (6). Heart transplants were accomplished in 103 neonates from 1985 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, neonatal recipients of heart transplantation have demonstrated better survival, a lower immunosuppressive burden, and less chronic rejection than their older counterparts (6). In 2001, West et al showed that ABO-incompatible heart transplants could be safely performed in infants due to the inability of the immature immune system to mount an effective response to carbohydrate antigens (7).…”
Section: Neonatal Immune Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…One of us (REC) (16) reviewed the dramatic progress made over three decades in the staged palliation and reconstruction of the hypoplastic left heart beginning with a modification of the procedure first described in 1980 by Norwood (23) or other procedures and culminating in a third major operation, the Fontan procedure, performed at 18 months to 4 years of age. Reconstructive procedures continue to evolve and newer approaches to reconstruction are debated today (14); however, physiology is never fully restored by these procedures.…”
Section: Some Approaches To the “Cure” Of Cardiac Failure In The Newbornmentioning
confidence: 99%